Identification of Trichoderma harzianum T3.13 and its interaction with Neoscytalidium dimidiatum U1, a pathogenic fungus isolated from dragon fruit (Hylocereus polyrhizus) in Malaysia - Wan Zulkifeli, Wan Rusmarini; Md Shah, Umi Kalsom; Abdullah, Mohd Puad; Mamat, Suhaila; Tan, Geok Hun (International Journal of Agriculture and Environmental Research, 2017)
Endophytes can produce enzymes which facilitate their initial colonisation of plant tissues and direct interactions with microbial pathogens. In this study, endophytic fungus from the stem of healthy dragon fruit (Hylocereus spp.) was successfully identified as Trichoderma harzianum T3.13. T. harzianum T3.13 was shown to have the ability to produce antagonistic activity against Neoscytalidium dimidiatum U1, a pathogen fungus from the stem of unhealthy dragon fruit. The chitinolytic activities of T. harzianum T3.13 were 0.194 U/ml in a medium containing 3% (w/v) of colloidal chitin as sole carbon source. Semi-quantitative RT-PCR was used to quantify the expression patterns of the genes during the interaction of T. harzianum T3.13 with pathogen N. dimidiatum U1 and control pathogen Colletotrichum gloeosporioides, respectively. The expression of the exc1 and chit42 genes were observed to be present before and after the interaction occurred in the presence of N. dimidiatum U1. However, the expression of the bgn13.1 gene increased after 24 hours up to 96 hours of interaction in the presence of N. dimidiatum U1. In the presence of C. gloeosporioides, the expression of bgn13.1 and chit42 gradually decreased during the interaction although the expression of the exc1 gene did not change. The results suggested that the endophytic fungus T. harzianum T3.13 has the potential as a good biological control agent against N. dimidiatum U1 and C. gloeosporioides. Thus, the study provided an insight into cellular and molecular interactions between T. harzianum T3.13 and pathogenic fungi.